(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the main difficulties faced by medical students in mastering anatomical terminology. The complexity of Latin and Greek-based anatomical terms, the large volume of terminology, and insufficient integration of anatomy with clinical disciplines pose significant challenges in the learning process. The study examines students’ levels of terminological competence, their ability to memorize anatomical terms, and their application in clinical practice. Furthermore, the effectiveness of traditional and modern teaching approaches in anatomy education is compared. To address the identified problems, the use of visual learning tools, clinical cases, interactive teaching methods, and digital educational technologies is recommended. The findings of the study contribute to the development of methodological recommendations aimed at improving the teaching and learning of anatomical terminology in medical education.